Primary Production of a Deciduous Forest at Varanasi - Singh, R. P.; Chaturvedi, O. P. (Indian Forester, 1983)
Primary productivity of six principal tree species constituting 65.1% of tree population and about 80% of the basal area of tree is examined for individual tree, species and density and area basis. The results are extrapolted to the remaining 20 species of the community. The method employed is based on harvesting of selected trees of differnt girth and measuring increment in girth of marked treeS for a period of one year. Mathematical models of increment in girth and corresponding biomass have been developed to estimate mean annual net productivity and the current annual net prductivity. Age of the trees in the natural stand was determined from regression analysis. It is shown that the method employed in forestry for determination of wood volume on the basis of mean aud current prodvctivities, grossly underestimates total productivity of the forest.